Desa dan Rumah Tangga Petani di Bawah Pembangunan: Kontekstualisasi Pemikiran Sodality S.M.P. Tjondronegoro dalam Agroekologi - Gutomo Bayu Aji (Sodality: Jurnal Sosiologi Pedesaan, 2021)
This article attempts to contextualize the concept brought forward by S.M.P. Tjondronegoro regarding rural social organization under development. The framework used by Tjondronegoro makes it possible to re-open the discussion on villages and peasants from the point of view of peasant household economic theory. The central question of this discussion remains similar to Tjondronegoro's previous concern, such as the participation of rural communities under development. These two approaches touch the basic theory that views participation from different angles. By using the concept of sodality as a cultural mediation space, where cultural agroecology is seen as a representation of the agency and actions of peasants, the issue of participation in rural development can be seen more broadly. This effort places Tjondronegoro's concept within the spectrum of agroecological science and movement.